Folgt nach "TTIP Leaks" nun doch "TTIP Light"? - Hayo Reimers (Wirtschaftsdienst, 2016)
Die Diskussion über die Transatlantische Handels- und Investitionspartnerschaft (TTIP) ist kontrovers. Durch die neuerdings bekannt gewordenen Veröffentlichungen zum Verhandlungsstand des TTIP-Abkommens (TTIP Leaks) ist aber eine bessere Beurteilung der Einzelfragen möglich. Der Autor untersucht, bei welchen kritischen TTIP-Komponenten ein Kompromiss denkbar und sinnvoll wäre, welche Themen so strittig sind, dass sie einen "TTIP Light"-Ansatz rechtfertigen würden, und ob das daraus resultierende Abkommen letztlich noch werthaltig wäre. – – The "TTIP Leaks" documents published by Greenpeace in Mai 2016 offered some new insides into the progress of TTIP negotiations and gave a new drive to public discussions on the issue. Although the value added in transparency produced by the Greenpeace papers is limited, it nevertheless seems to support the more critical opinion on TTIP. By building up pressure from the public, it reduces the probability to successfully finalize the ongoing negotiations within the intended timeframe and fosters the idea to agree on some form of "TTIP Light" rather than letting the negotiations fail completely. Based on available information including the Greenpeace papers, this article tries to analyze the most critically discussed elements of TTIP with a view to rationalize a decision on compromising on any of these components or on dropping some of them altogether in favor of a reduced "TTIP Light" solution.
Keywords: F21; F53; K33; 330; Handelsabkommen; Mediale Berichterstattung; Kritik; Diskurstheorie; TTIP-Staaten